1999
DOI: 10.5194/hess-3-429-1999
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of the solute transport volume in biodegraded municipal solid waste

Abstract: Abstract. A large undisturbed sample (3.5 m3) of 22-year-old, biodegraded solid waste set up to estimate the volume fraction participating in the transport of solutes through the waste material. Altogether, five tracer tests were performed under ponding and sprinkling conditions, and under steady-state and transient conditions. The experimental break through curves (BTCs), which indicated a non-equilibrium transport of the solute by early peaks and long right-hand tails, were used to parameterize log-normal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
4
20
1
Order By: Relevance
“…Since bromide was flushed as an indigenous contaminant, a comparative mass-balance could not be made. Further corroborating evidence is given in Woodman & Beaven (2011) who demonstrated that the lithium tracer results of Rosqvist and Bendz (1999) could also be consistent with a mass-loss of lithium in a degraded MSW.…”
Section: Tracer Mass Balancesupporting
confidence: 62%
See 1 more Smart Citation
“…Since bromide was flushed as an indigenous contaminant, a comparative mass-balance could not be made. Further corroborating evidence is given in Woodman & Beaven (2011) who demonstrated that the lithium tracer results of Rosqvist and Bendz (1999) could also be consistent with a mass-loss of lithium in a degraded MSW.…”
Section: Tracer Mass Balancesupporting
confidence: 62%
“…The tests were all run for approximately a month (in the range 26 to 45 days). Lithium has been used several times as a tracer for transport within MSW (Blakey et al, 1998;Öman and Rosqvist, 1999;Rosqvist & Bendz, 1999;Beaven et al, 2003). Its common use in MSW is explained by its relatively low cost and frequently low background concentration (Harris, 1979;Blakey et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…There have been a few previous column tracer tests on saturated methanogenic MSW wastes that were suggestive of dual-porosity processes (Beaven et al, 2003;Rosqvist & Bendz, 1999;Fellner & Brunner, 2010). However, difficulties in hydraulic control (specifically, flow rate and saturation level) meant that they were not entirely conclusive (Woodman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has been used several times as a tracer for transport within MSW (Blakey et al, 1998;Öman and Rosqvist, 1999;Rosqvist & Bendz, 1999;Beaven et al, 2001;Beaven et al, 2003). Its common use in MSW is explained by its relatively low cost and commonly low background concentration (Harris, 1979;Blakey et al, 1998).…”
Section: Lithiummentioning
confidence: 99%
“…The dry bulk density of the refuse was estimated at both sites using the known volume of each landfill, the known mass of waste deposited, and measurements or estimates of the initial moisture content of the waste. The porosity was not measured, but was estimated to range between 0.45 and 0.55, based on a survey of typical refuse porosities published in the literature (Owesis et al, 1990;Zeiss and Major, 1993;Powrie and Beaven, 1999;Risqvist and Bendz, 1999). Thus, estimates of M c from PGTT exhibit greater uncertainty than estimates of S w , due to uncertainties in q d b and n. Moisture contents measured with PGTTs were in very good agreement with available gravimetric measurements at these field sites, with the estimated M c from PGTTs within 10% of gravimetric values.…”
Section: Field Applicationsmentioning
confidence: 99%